Birokrasi Weberian: “Proportional Approach” - Surur, Midkholus (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2019)
Weberian bureaucracy theory is a bureaucratic theory that is very influential on all countries both those who embrace democracy and authoritarianism. Weber sees that bureaucratic performance can be approached from social behavior theory. To know and explain human behavior, it must first know the intent and purpose of the behavior. Weber distinguishes the motives behind human behavior, namely affective, traditional, value rational and instrumentally rational. Instrumentally rational is the guideline in the behavior of Weber's bureaucracy. Weber further stated, authority is not formed and implemented by itself. In order to create a legal authority there are five creeds that must be used as guidelines. The five creeds are as follows: Legitimate rules, law is an abstract, impersonal system of rules, which obeys the law only as members of the bureaucracy, obedience not to the person holding authority but to the impersonal rule of law. Based on the five conceptions, Weber formulated eight propositions regarding the formulation of legal authority namely: official duty regulation, task specialization, hierarchical, technical-legal, impersonal, written, administrative-bureaucratic staff. This theory is considered by many political experts and governments to have a number of weaknesses. These weaknesses are a hierarchical bureaucratic structure, a military-like organizational system, excessive emphasis on the legalformal aspect, unit specialization, bureaucratic employees who are not neutral and bureaucratic employees who are less representative. Besides these weaknesses, Weber's bureaucratic theory has made a positive contribution in the process of implementing governance today, namely the impersonal system, the contract system for employees, the career system and the focus on one position.